Long-term olfactory function outcomes after pituitary surgery by endoscopic endonasal transsphenoidal approach. Issue 2 (April 2020) - Kuwata, Fumihiko; Kikuchi, Masahiro; Ishikawa, Masaaki; Tanji, Masahiro; Sakamoto, Tatsunori; Yamashita, Masaru; Matsunaga, Mami; Omori, Koichi; Nakagawa, Takayuki
Abstract: Objectives: To evaluate long-term olfactory outcomes in patients who underwent pituitary surgery through the endoscopic endonasal transsphenoidal approach (EETSA) by T&T olfactometer. Methods: We retrospectively reviewed 26 patients who underwent pituitary surgery via EETSA. Olfactory function was assessed by T&T olfactometer before and 6 months after surgery. The mean of recognition thresholds for five different odorants was used. The change in the mean recognition threshold values was evaluated in the entire cohort and the subgroup analysis was performed according to the age, sex, past history of pituitary surgery (primary surgery or revision surgery), histopathology (non-functioning adenoma (NFA) or functioning adenoma (FA)), reconstruction procedure (rescue flap or nasoseptal flap), and superior turbinate management (preserved or resected). Results: Of the 26 patients (12 men and 14 women, median age 53 years), 21 patients were newly diagnosed with pituitary gland tumor (16 NFAs, 5 FAs) and the remaining 5 were diagnosed with recurrent pituitary gland tumor (4 NFAs and 1 FA). In the whole cohort, the mean recognition threshold values of T&T olfactometer significantly improved after surgery (P = 0.01). Thirteen out of 26 patients (50%) showed olfactory improvement, whereas only 3 (12%) showed deterioration. In the subgroup analysis, olfactory function outcomes were not significantly different between the subgroups with respect to the age, sex, past history of pituitary surgery, histopathology, reconstruction procedure, or superior turbinate management. The olfactory function tended to worsen in the revision surgery group compared to that in the primary surgery group, but not significantly (P = 0.06). Conclusions: The olfactory function was improved or maintained after pituitary surgery via EETSA in 88% of patients, indicating the benefits of low invasiveness of our surgical treatment. On the other hand, three patients (12%) demonstrated deterioration of olfactory function, suggesting that the risk of postoperative olfactory dysfunction should be informed to patients.